The anti-witchcraft ritual Maqlû : the cuneiform sources of a magic ceremony from ancient Mesopotamia - Schwemer, Daniel (Harrassowitz Verlag, 2017)
"This book examines the epigraphy and history of transmission of the cuneiform sources of the Maqlû anti-witchcraft ritual, one of the major compositions of ancient Mesopotamian exorcistic lore and a masterpiece of Babylonian literature ... The origins of this book go back to a time when anyone who wanted to read the text of Maqlû had to make do with Gerhard Meier's composit 1937 edition, and the examination of individual manuscripts was possible only for those who studied the original clay tablets at the British Museum and in other collections around the world."--Page [vii].